PENELUSURAN SISTEM KEPERCAYAAN SUKU DOHOI (ANAK SUKU OT DANUM) DI TUMBANG SAMBA KABUPATEN KATINGAN KALIMANTAN TENGAH - Liadi, Fimeir (PALITA, 2017)
This research started from the desire to do Dawah Islamiyah to the inland residents of Central Kalimantan, especially to the Dayaks who have the power of Exotic Drag to be studied and dii through the door of their social culture. Actually the belief system is a form of human conquest of humanity to something great, all-powerful and all-great. The Dohoi tribe that is part of the Ot Danak Dayak tribe has a peculiarity in the order of life of his belief, although they have adherence to the Dayak conviction of Kaharingan belief. The Dohoi tribe as adherents of the Helu religion (ancient religion) continue to hold rituals of Kaharingan faith even though they have embraced other religions such as Protestant, Catholic and Moslem. It is interesting to examine in order to express their strong sense of belief and has survived almost 2 centuries of Kaharingan faith development by its adherents in Central Kalimantan. The results showed that the Dohoi tribe is a follower of syncretism in which their beliefs (Kaharingan) are believed to be the dominant religious teachings they use ie Hindu, Buddhist, Christian / Catholic and Moslem.